COMPARATIVE ANALYSIS OF ONLINE TRANSACTION BETWEEN PRIVATE AND PUBLIC SECTOR BANKS - Shukla, Gajendra V.; Madhuri Puranik (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The comparative analysis of online transactions between private and public sector banks examines the differing operational models, customer engagement strategies, performance metrics, and regulatory impacts that characterize each sector’s approach to digital banking. As the financial landscape has evolved due to technological advancements and shifting consumer preferences, understanding these distinctions has become increasingly vital. Private sector banks have leveraged their agility and innovative practices to enhance customer experience and capture market share, while public sector banks focus on broader outreach and equitable access to financial services, often at the expense of speed and personalization. Notable differences between the two sectors manifest in their operational frame works, where private banks typically adopt more flexible and tech-driven solutions compared to the more bureaucratic structures of public banks. This distinction influences customer engagement, with private banks emphasizing personalized services and advanced digital tools, attracting a significant portion of the market, particularly among younger demographics who prefer efficient online experiences. Research indicates that approximately 49.2% of consumers favor private banks for their primary transactions, citing superior service quality as a key factor in their choice. Despite their strengths, both sectors face significant challenges and opportunities in the realm of online banking. Private Banks must navigate the competitive landscape shaped by fintech innovations and evolving consumer expectations, while public banks contend with regulatory constraints that can hinder rapid technological adaptation. Furthermore, the regulatory environment governing online banking impacts both sectors’ operational effectiveness, with ongoing discussions about open banking highlighting the need for reforms that enhance consumer choice and innovation.